Phytoplankton composition, dominance and abundance as indicators of environmental compartmentalization in Jurumirim Reservoir (Paranapanema River), Sao Paulo, Brazil - Nogueira, Marcos Gomes (My University, 2000)
Patterns in the spatial and temporal composition, dominance and abundance of the phytoplankton community of the Jurumirim Reservoir (Brazil) were studied during one year at ten different sampling stations. The main phytoplankton associations were characterized by diatoms and blue-green algae, in distinctive patterns of dominance. The main species were Microcystis aeruginosa Kuetz, Anabaena circinalis Rabenhorst, A. spiroides Kleb., A. solitaria Kleb., Aulacoseira cf. italica Grunow and A. granulata (Ehr.) Simon. A high growth of Aulacoseira was observed in the upstream zones of the reservoir in spring, at the beginning of the seasonal rainy period. This growth was a response to increased flow rates and input of fresh nutrients by the main feeder rivers. A high concentration of bluegreen algae, especially Anabaena circinalis and A. spiroides, was observed in winter (dry season) in the lacustrine part of the reservoir, towards the dam. These algae benefitted from the longer water retention times and greater internal circulation of nutrients in the absence of a thermocline at this time of the year. Among the Cyanophyceae, there was an alternation between M. aeruginosa, more abundant in summer, and Anabaena, dominant in autumn and winter. A conspicuous growth of Anabaena occurred in a diverticle of the reservoir, sheltered from the main advective processes that predominate in the central channel. Higher phytoplankton diversity was associated with the contact zone between riverine and lacustrine systems.
Keywords: Large reservoir; Phytoplankton composition and abundance; Spatial distribution; Temporal distribution; Tropical latitude